Thursday

April 24, 2014

April 24, 2014

Posted by **renee** on Thursday, November 4, 2010 at 9:51pm.

- calculus -
**Reiny**, Thursday, November 4, 2010 at 10:52pmnotice that n^2-1 = n(n+1)(n-1)

so the LCD is n^2-1

multiply by the LCD

10 + (2n-5)(n+1) = (2n+5)(n-1)

10 + 2n^2 -3n - 5 = 2n^2 +3n - 5

10 = 6n

n = 5/3

**Related Questions**

algebra - So... I know the answer to the question because it's something we ...

Abstract Algebra - If 2^n>n^2 and n>5, then 2^n+1>(n+1)^2 Proof: ...

HELP. - Choose a formula for the nth term of the sequence: a2 , a4 , a6 , ... 2 ...

calculus - For large values of n, the Riemann sum 1/n(sin0 + (pi/2n) + sin(2pi/...

algebra - Please explain a little bit further 4(5^(2n+1))-10(5^(2n-1))/ ( 2(5^n...

data management - 1) show that a) 2(2n-1 C n-1) = (2n Cn) b) n(2n C n) = (n+1)(...

Pre-cal - use mathematical induction to prove that 1^2 + 2^2 + 3^2 + ... + n^2...

bobpursley, math,correction - Let n be a postive integer, then n+1 is the next ...

math - 14m^2n - 6m^2n = 14-6=8 8m^2n

algebra 1 HELP - simply show each step (4n^2-4/1+n^2)(1-n/2n)(1-2n^2+n^4/2+2n) ...